Push-off forces in elite short-track speed skating - van der Kruk, E.; Reijne, M. M.; de Laat, B.; Veeger, D. (Sports Biomechanics, 2019)
This study performed an analysis of the push-off forces of elite-short-track speed skaters using a new designed instrumented short-track speed skate with the aim to improve short-track skating performance. Four different skating strokes were distinguished for short-track speed skaters at speed. The strokes differed in stroke time, force level in both normal and lateral directions, and the centre of pressure (COP) on the blade. Within the homogeneous group of male elite speed skaters (N = 6), diversity of execution of the force patterns in the four phases of skating was evident, while skating at the same velocities. The male participants (N = 6) with a better personal record (PR) kept the COP more to the rear of their blades while hanging into the curve (r = 0.82, p < 0.05), leaving the curve (r = 0.86, p < 0.05), and entering the straight (r = 0.76, p < 0.10). Furthermore, the male skaters with a better PR showed a trend of a lower lateral peak force while entering the curve (r = 0.74, p < 0.10). Females showed a trend towards applying higher body weight normalised lateral forces than the males, while skating at imposed lower velocities.